Research Integrity and Methodological Maturity of Accounting Science: Interconnection, Challenges And Vectors of Development - Kashchena, Nataliia; Vasylishyn, Stanislav (Herald of Economics, 2026)
Contemporary challenges require the academic environment to overcome intellectual formalism. Research into the synergy between methodological maturity and the researcher’s ethical agency is becoming increasingly relevant as a basis for knowledge verification within the convergent system of accounting science. Research objective - to substantiate the conceptual foundations of the interconnection between research integrity and methodological maturity, to identify contemporary challenges and determine strategic vectors for the development of accounting science as an effective tool for building an ethical economic environment. Used in the research process: a systematic approach was applied to define accounting science as a convergent system; theoretical generalisation – to develop a research integrity profile; logical modelling – to construct a conceptual quality-assurance model; deduction – to identify challenges and strategic development vectors. Methodological maturity is demonstrated to be a dynamic system evolving from reproductive mastery of methods to architectural knowledge design, contingent on equal synergy with research integrity. A research integrity profile has been developed according to the stages of accounting cognition. An original conceptual model has been constructed, the core of which is the researcher’s ethical and methodological profile, enabling the transformation of accounting science from a collection of static knowledge into a predictive instrument for minimising professional risks and information asymmetry. Strategic vectors for accounting science as a guarantor of stability and transparency in the modern economic environment have been articulated. Further research targets adaptation of the ethical and methodological profile to digitalisation conditions and development of transparency protocols for post-war national economic recovery.